Effect of high glucose-induced hyperglycemia on Viral Haemorrhagic Septicaemia Sirus (VHSV) infection in adult zebrafish - Cuong, Tran Van; Thoa, Nguyen Thi (Vietnam Journal of Science and Technology, 2020)
This study, we conducted a high glucose immersion protocol to induce hyperglycemic zebrafish, later on, with the aim to evaluate the relationship between hyperglycemia and VHSV infection using the zebrafish model. As the results, zebrafish immersed in a 2000 ppm glucose solution for 10 days, FBG has increased two times as compared to control. In addition, hyperglycemic zebrafish was more susceptible to the virus infection resulted in increased the viral mRNA expression levels as well as the viral copy number as 1.7 Log higher than control.